2003
DOI: 10.1177/095632020301400203
|View full text |Cite
|
Sign up to set email alerts
|

N4-Acyl-Modified D-2′,3′-Dideoxy-5-Fluorocytidine Nucleoside Analogues with Improved Antiviral Activity

Abstract: A series of 2',3'-dideoxy (D2) and 2',3'-didehydro-2',3'-dideoxy (D4) 5-fluorocytosine nucleosides modified with substituted benzoyl, heteroaromatic carbonyl, cycloalkylcarbonyl and alkanoyl at the N4-position were synthesized and evaluated for anti-human immunodeficiency virus type 1 (HIV-1) and anti-hepatitis B virus (HBV) activity in vitro. For most D2-nucleosides, N4-substitutions improved the anti-HIV-1 activity markedly without increasing the cytotoxicity. In the D4-nucleosides series, some of the substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…In the presence of tet, undetectable levels of virus were observed in cell culture supernatant, whereas in the absence of tet high titres of HBV were observed (Ladner et al, 1997). Subsequent studies have shown the utility of HepAD38 cells for drug discovery and development against HBV (Bijsterbosch et al, 2001;Shi et al, 2003;Ying et al, 2003). In this report, HepAD38 cells transplanted subcutaneously into nude mice resulted in the development of high virus titres in blood.…”
Section: ©2007 International Medical Press 0956-3202mentioning
confidence: 65%
“…In the presence of tet, undetectable levels of virus were observed in cell culture supernatant, whereas in the absence of tet high titres of HBV were observed (Ladner et al, 1997). Subsequent studies have shown the utility of HepAD38 cells for drug discovery and development against HBV (Bijsterbosch et al, 2001;Shi et al, 2003;Ying et al, 2003). In this report, HepAD38 cells transplanted subcutaneously into nude mice resulted in the development of high virus titres in blood.…”
Section: ©2007 International Medical Press 0956-3202mentioning
confidence: 65%
“…In the presence of Tet, virus replication was suppressed, while in the absence of Tet, very high titers of HBV were observed (29). Subsequent studies have shown the utility of this cell line for drug discovery and the development of lead compounds active against HBV (41). Previously, we demonstrated that HepAD38 cells transplanted subcutaneously into nude mice resulted in the development of viremia, and treatment of these mice with drugs active against HBV demonstrated significant antiviral activity in vivo, suggesting that this simple small-animal model could be used to assess new therapeutic approaches and combination therapies against wild-type (wt) HBV (17).…”
mentioning
confidence: 99%